Phylogenetic autocorrelation and evolutionary interpretation of the higher-taxon approach for biodiversity analyses - Diniz-Filho,J. A. F. (2006)
Although in most recent broad-scale analyses, diversity is measured by counting the number of species in a given area or spatial unity (species richness), a `top-down' approach has been used sometimes, counting higher-taxon (genera, family) instead of species with some advantages. However, this higher-taxon approach is quite empirical and the cut-off level is usually arbitrarily defined. In this work, we show that the higher-taxon approach could be theoretically linked with models of phenotypic diversification by means of phylogenetic autocorrelation analysis in such a way that the taxonomic (or phylogenetic) rank to be used could not be necessarily arbitrary. This rank expresses past time in which taxa became independent for a given phenotypic trait or for the evolution of average phenotypes across different traits. We illustrated the approach by evaluating phylogenetic patches for 23 morphological, ecological and behavioural characters in New World terrestrial Carnivora. The higher-taxon counts at 18.8 mya (S L) defined by phylogenetic correlograms are highly correlated with species richness (r = 0.899; P < 0.001 with ca. 13 degrees of freedom by taking spatial autocorrelation into account). However, S L in North America is usually larger than in South America. Thus, although there are more species in South and Central America, the fast recent diversification that occurred in this region generated species that are "redundant" in relation to lineages that were present at 18.8 my. BP. Therefore, the number of lineages can be comparatively used as a measure of evolutionary diversity under a given model of phenotypic divergence among lower taxonomic units.